Studi Intensitas Cahaya Dan Cendawan Mikoriza Arbuskula Pada Permudaan Alam Ramin (Gonystylus Bancanus (Miq.) Kurz) (Study on Arbuscular Mycorrhizal Fungi and Light Intensity to the Natural Regeneration of Ramin (Gonystylus bancanus (Miq.) Kurz)) - Abdurrani Muin; Yadi Setiadi; Sri Wilarso Budi; Irdika Mansur; Endang Suhendang; Supiandi Sabiham (Institut Pertanian Bogor (IPB University), 2006)
The objective of this research is to find out the early information of optimum light intensity and highest mycorrhizal colonization on natural Ramin seedling which it includes in semitolerant plant. The research was conducted in Ramin Natural Forest of Sungai Pelunjung Labai, Sanggau District, West Kalimantan for a year. The results of the research show that there are correlations between light intensity with mycorrhizal colonization. Ramin seedling which grown under the light intensity 3190 – 9500 lux have high mycorrhizal colonization and their growth better than the other treatment. Meanwhile Ramin seedling which grown in closed area or in open area with light intensity less than 1670 lux and more than 10840 lux respectively have lower mycorrhizal colonization and their growth was lower.Key words: Ramón seedling (G. bancnus), Light intensity and Mycorrhizal Fungi